Pharmacokinetic/pharmacodynamic modeling for dose selection for the first‐in‐human trial of the activated Factor XII inhibitor garadacimab (CSL312). Issue 3 (8th December 2021) - Pawaskar, Dipti; Chen, Xi; Glassman, Fiona; May, Frauke; Roberts, Anthony; Biondo, Mark; McKenzie, Andrew; Nolte, Marc W.; Jusko, William J.; Tortorici, Michael
Abstract: Factor XII (FXII) is a serine protease involved in multiple cascades, including the kallikrein–kinin system. It may play a role in diseases in which the downstream cascades are dysregulated, such as hereditary angioedema. Garadacimab (CSL312) is a first‐in‐class, fully human, monoclonal antibody targeting activated FXII (FXIIa). We describe how translational pharmacokinetic (PK) and pharmacodynamic (PD) modeling enabled dose selection for the phase I, first‐in‐human trial of garadacimab. The PK/PD data used for modeling were derived from preclinical PK/PD and safety studies. Garadacimab plasma concentrations rose with increasing dose, and clear dose‐related PD effects were observed (e.g., a mechanism‐based prolongation of activated partial thromboplastin time). The PK/PD profile from cynomolgus monkeys was used to generate minimal physiologically‐based pharmacokinetic (mPBPK) models with target‐mediated drug disposition (TMDD) for data prediction in cynomolgus monkeys. These models were later adapted for prediction of human data to establish dose selection. Based on the final mPBPK model with TMDD and assuming a weight of 70 kg for an adult human, a minimal inhibition (<10%) of FXIIa with a starting dose of 0.1 mg/kg garadacimab and a near maximal inhibition (>95%) at 10 mg/kg garadacimab were predicted. The phase I study is complete, and data on exposure profiles and inhibition of FXIIa‐mediated kallikrein activity observed in the trial support and validate these simulations. This emphasizes the utility and relevance of translational modeling and simulation in drug development.